Welcome to the Desert of the Code!: Empty Images and “Digital Seeing” - Grampp, Sven (Taylor and Francis, 2025)
In this chapter, Sven Grampp claims that even if there seems to be hardly any need for legitimizing the study of images as their effects on viewers are becoming a signature of our age under the signum of visual culture, it should be emphasized that many popular digital image types are, at least as far as their visual potency is concerned, remarkably weak, “poor”, image-skeptical, seeming to be only registrations, or even empty, devoid of any significant agency. For all types of images mentioned in this chapter-agency photos, memes, GIFs, surveillance images, and generative images-it is not the specific power of visuality that makes them properly “acting” but the fact that they either refer to something outside the image or invalidate the visual power of an image intrinsically. Thus, ironically, in the state of their omnipresence, images in media history became today what researchers like W.J.T. Mitchell and Horst Bredekamp have always struggled against, namely, code-like or even empty sleeves.
CRIS-Team Scopus Importer:2025-11-28